Association between Polymorphisms of Mtr Gene Rs1805087 and Coronavirus Infection - KurbonovaZ.Ch; BabadzhanovaSh.A; InoyatovaF.Kh; Filiz Erdogan M; Sayfutdinova Z.A; Tojiboyeva D.A. (Global Scientific Publishing, 2023)
The most serious COVID-19 side effects brought on by SARS-CoV-2 infection is hypercoagulopathy-induced ischemia damage to important organs, which frequently results in COVID-19 infection-related impairment and death in patients. Therefore, it is possible to lower the above-mentioned indicators of morbidity and mortality by carefully examining the factors that contribute to hypercoagulopathy, selecting patients who are predisposed to the emergence of this pathological process, and performing specialized proliferative and therapeutic procedures for them. The MTR gene polymorphisms, which are thrombophilic genes and one of the causes of hypercoagulopathy, have been studied in COVID-19-infected Uzbek patients to better understand the relationship between the alleles of these genes and the amount of homocysteine in these patients as well as the role they may play in the pathogenesis of COVID-19.
Keywords: MTR; rs1805087; wild allele; minor allele folate cycle